O professor e o ensino de leitura: Uma reflexão sobre a formação continuada - Delalana, Maria do Carmo Zanaro (2006)
The objective of this dissertation is to reflect on the relationship between teachers and reading concepts dealt in a program of continuing education. Our questioning over practice and teaching theory has led us on the need of such reflection. We organized the text in three chapters. In the first chapter, initially, we will make a theoretical description of reading from the interactional perspective based on social and cognitive aspects; then we will elaborate an analysis about our current teaching situation on reading and at last we will reflect on the teacher s reading. So that we show the material used for the analysis, there is a description in the second chapter of the program of continuing graduation from the course books used in the program and questions aimed to the teachers. In the third chapter, we will reflect about two quotations presented in the course book, about the teacher s responses and about the reading concepts having in mind the interaction between such concepts and the mother language teachers. Our initial hypothesis that would explain the disarticulation between theory and practice, concerning how the theories came to the teachers, was partially confirmed